“We wanted our children should have it better”: Jewish Medical Students at the University of Toronto, 1910-51 - Millar, W. (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association/La Société historique du Canada, 2000)
AbstractThis article traces the development of a large contingent of Jewish students among those enrolled in the Faculty of Medicine at the University of Toronto from 1910 to mid-century. During most of this period, unlike many other North American universities, Toronto imposed no quotas on Jewish entrants, nor any systematic barriers to their academic progress. Many of them found the university's medical school an educational niche, and a relatively rare opportunity to acquire the means to make a respectable professional living. The students' socio-economic backgrounds and academic careers before and during medical school help to illuminate that experience. By examining the peculiar intersection of university policies and the political culture of the province, the article also seeks to explain why, over most of the period, the University of Toronto maintained the principles of accessibility and opportunity for all, despite the prevalence of anti-Semitic attitudes in the larger Canadian society.